2010
DOI: 10.1016/j.socscimed.2009.10.048
|View full text |Cite
|
Sign up to set email alerts
|

How does violence exposure affect the psychological health and parenting of young African-American mothers?

Abstract: Urban, minority, adolescent mothers are particularly vulnerable to violence exposure, which may increase their children’s developmental risk through maternal depression and negative parenting. The current study tests a conceptual model of the effects of community and contextual violence exposure on the mental health and parenting of young, African American mothers living in Washington DC. A path analysis revealed significant direct effects of witnessed and experienced violence on mothers’ depressive symptoms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 87 publications
3
29
0
Order By: Relevance
“…Our study does not answer the question of how violence affects healthcare utilization, but it is proposed to disrupt caregiver coping strategies and erode decision-making competencies. 20 Research in traumaexposed populations shows that low-income urban caregivers often lack adequate resources to cope with traumatic experiences, leaving them vulnerable to depressive symptoms 39 and difficulties in fulfilling caregiving activities such as attending to their child's needs. 40 Caregivers who experience chronic exposure to traumatic events are at even greater risk for decreased parental effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Our study does not answer the question of how violence affects healthcare utilization, but it is proposed to disrupt caregiver coping strategies and erode decision-making competencies. 20 Research in traumaexposed populations shows that low-income urban caregivers often lack adequate resources to cope with traumatic experiences, leaving them vulnerable to depressive symptoms 39 and difficulties in fulfilling caregiving activities such as attending to their child's needs. 40 Caregivers who experience chronic exposure to traumatic events are at even greater risk for decreased parental effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the presence of poverty and/or absence of social capital, caregivers are more likely to experience psychological distress, mental health concerns, or substance abuse problems, which may impair a caregiver's abilities to parent. The ability to effectively parent can act as a buffer between his or her child and the damaging effects of a violent and unsafe place of residence (Brunette and Dean 2002;Gewirtz et al 2009;Mitchell et al 2010;Weinreb et al 2006). Conversely, caregiver mental health or substance abuse problems can mediate or moderate the association of the pathways between contextual factors and child mental health and exposure to maltreatment (Li et al 2011;Manly et al 2013;Martin et al 2012).…”
Section: Influences Of Community Adversity and Caregiver Well-being Omentioning
confidence: 99%
“…As a potentially chronic source of social stress, day-to-day experiences of ethnic discrimination may negatively influence young, African American mothers' psychological health and parenting behavior (Brody et al, 2008;Mitchell et al, 2010;Simons et al, 2002;Williams, Neighbors, & Jackson, 2003;Williams & Williams-Morris, 2000). For example, Brody et al (2008) found that African American mothers' reports of discrimination were associated with subsequent increases in depressive symptoms, which in turn predicted decreases in competence-promoting parenting.…”
Section: Contextual Stressors Faced By Young African American Mothersmentioning
confidence: 99%